Influence of Seasonality on Accommodation Facilities' Capacity Planning - Laco, Peter (Wpływ sezonowości na planowanie możliwości zakwaterowania, 2009)
Comparing contemporary tourism to the situation a few years ago, we can see various differences. New places are becoming attractive as a destination, the length of stay is changing. The differences are caused by various reasons like changes in demographic structure, information sharing, currency strengthening and others. Several studies and papers point out the potential of central and eastern European countries and that is why we focused in our paper on tourism business, particularly on accommodation facilities in Banská Bystrica, Slovakia. We discuss the current state of capacities available and the influence of seasonality, because this feature seems to be one of the most important factors influencing the capacity planning.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 42-47